Superimposed pilot-based channel estimation method combined with user scheduling for large-scale MIMO system - Jie LI; Xiaorong JING (Dianxin kexue)
Time division multiplexing method is commonly used in conventional channel estimation, which results in poor efficiency of bandwidth usage. Additionally, the available pilot resources are finite due to the limited channel coherence time, and the pilot sequences must be multiplexed between the neighbor cells, which leads to problems of pilot contamination. To solve these problems above, superimposed pilot-based channel estimation method combined with user scheduling was proposed. In the method, the users in different cells were cooperatively scheduled and assigned the same pilot by optimizing the factor of power allocation and using the signal to leakage and noise ratio （SLNR）as measure metric. Simulation results demonstrate the validity of the proposed method.